The Law of Contract in Ghana - Dowuona-Hammond, C. (My University, 2011)
Contracts are made by people every day, whether the parties recognise it or not. Each time one spends money on anything – a bus ticket, an airline ticket, a pair of shoes, a meal in a restaurant, laundry services, books, or signs a lease, etc. one concludes a valid and legally binding contract. Contracts may be oral or written; may arise by parties’ conduct; may involve large or trivial sums of money and may be of short or long duration. The contents and subject matter of the contract also vary widely, creating different kinds of contracts including contracts of sale, hire purchase, insurance, employment, marriage, mortgage, leases etc. The Law of Contract is simply the branch of the Law, which governs the effort to achieve and carry out voluntary agreement. The principles of the law of contract are concerned with determining whether an agreement or transaction is binding or legally enforceable and if so, what the consequences of a breach of it are.